Temporal variation of voids in waxy crude oil gel in the presence of temperature gradient. Issue 10 (2nd October 2020) - Chala, Girma T.; Sulaiman, Shaharin A.; Japper-Jaafar, Azuraien; Abdullah, Wan Ahmad Kamil Wan
Abstract: The formation of voids is eminent below the pour point temperature of waxy crude oil. This paper discusses the temporal variation of voids in waxy crude oil gel in the presence of temperature gradient between the waxy crude oil and its ambient condition. Cooling of waxy crude oil to an end temperature of 10 °C was performed in a flow loop rig, after which it was scanned in a 3 T Magnetic Resonance Imaging (3 T-MRI) system. Five consecutive scans with equal intervals were taken and analyzed to observe the variation of voids over the waiting duration. It was observed that the percentage of total voids volume reduced from 7.16% to 6.09%, from 6.59% to 5.71% near a pipe wall, and from 0.57% to 0.38% around a pipe core at waiting duration of 50 minutes. A waiting duration of 10 minutes reduced the voids volume around the pipe wall from 6.59% to 6.33%, and this was the maximum when compared with observations at higher waiting durations. The rate of voids disappearance was also higher at shorter waiting durations, with a maximum of 0.032%/min rate of change of voids observed at 10 minutes. Conversely, a minimum of 0.002%/min rate of change of voids was observed at 40 minutes waiting duration, beyond which the difference was almost insignificant. The disappearance rates were small that the change in voids volume became minimal over longer waiting durations, showing insignificant voids variation with surrounding weather conditions.